Students’ Responses toward Hybrid and Online SPADA UNTIRTA in Teaching ESP for Economic Students at Sultan Ageng Tirtayasa University - Welliam Hamer; Nur Azmi Rohimajaya; Ledy Nur Lely (Journal of English Education Studies, 2025)
This study investigates students’ responses toward the implementation of hybrid and online SPADA UNTIRTA in teaching English for Specific Purposes (ESP) to first-semester economics students at Sultan Ageng Tirtayasa University. The research employed a qualitative-descriptive design, combining Likert-scale questionnaire data with open-ended student feedback and classroom observations. Two different learning modalities were compared: a hybrid model that blends face-to-face classroom sessions with asynchronous SPADA activities, and a fully online model that delivers all instruction via the SPADA platform. Findings reveal that students in the hybrid class responded positively to direct interaction with the lecturer, structured learning guidance, and the opportunity for peer collaboration. Meanwhile, students in the online class appreciated the flexibility and independence afforded by the digital platform but also reported challenges such as a lack of real-time feedback and reduced motivation. The results suggest that while both learning modes support student engagement in different ways, the hybrid model is more effective in maintaining interpersonal connection and motivation, while the online model is more suitable for self-regulated learners. These insights underscore the importance of aligning instructional design with learner preferences and capacities. Practical implications include integrating synchronous elements into online courses and providing learner training to optimize the process of delivering ESP materials in hybrid and online models.